PENGARUH PROMOSI JABATAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HOTEL HARRIS VERTU YELLO HARMONI JAKARTA - Lintang Ida Aisah; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the independent variable namely promotion, work dicipline, and work motivation of the dependent variable, namely worrk productivity. Design/methology/approach- The study was conducted using quantitative descriptive techniques, which collect data employee who working at Harris Vertu Yello Harmoni Jakarta by distributing questionare to 95 respondens. The results of this test were analyzed by the Multiple Linier Regression method using SPSS Statistic 20.00. The analysis technique used was by testing the validity and realibility, the classical assumption test in the form of normality test, multicolinearity test, heteroscedasticity, multiple linear regresion analysis and hyphotesis testing in theform of test (test, correlation test (R) and coefficient of determination (R2). Findings- The result showed that there was a significant influence between the variables of promotion, work diciplin, and work motivation influence to work productivity in Hotel Harris Vertu Yello Harmoni Jakarta.